Priorities in reducing child mortality: Azithromycin and other interventions. - David Mabey; Uduak Okomo; Brian Greenwood (PLoS Medicine)
In this Perspective, David Mabey and colleagues discuss a recent PLOS Medicine article on azithromycin as an intervention for reducing child mortality.